DEVELOPMENT STRATEGY PORT OF BIAS MUNJUL IN TOURISM RECOVERY AT THE POST COVID-19 - Kusuma, I Gede Wahyu; Dwijendra, Ngakan Ketut Acwin; Yudantini, Ni Made (Universitas Ibn Khaldun Bogor, 2022)
Indonesia implements Large-Scale Social Restrictions (PSBB) which are enforced per region based on the severity of the outbreak and the assessment is determined by the central government through the Ministry of Health. Restrictions on activities for traveling have a great impact on areas that utilize the tourism industry. Restrictions on activities lead to a decline in the economy of the community, especially in areas that rely on the tourism industry. Infrastructure has an important role in efforts to recover the economy and tourism after the pandemic. The infrastructure used as the object of research is the project Port Munjul Bias, which is one of the ongoing port projects on Ceningan Island. The purpose of the study was to look at the strategy for developing the Port Bias Munjul in the post-Covid-19 pandemic recovery. The type of research used is qualitative research with descriptive data presentation. The approach used is a SWOT analysis to see the strategy for developing the Port Bias Munjul in the midst of the Covid-19 Pandemic. The results obtained are the construction of the Port Bias Munjul in prime condition (SO), which shows that the existence of the Port Bias Munjul project will play a very important role in the recovery of tourism and the economy in Nusa Ceningan or its surroundings. Strategies that can be carried out are in the form of cooperation between local governments and the private sector, empowerment of local communities and improvement of logistical support facilities.